Report 7: Employee Welfare and Benefit Programs, Proceedings of a Conference, November 1950 - Chartier, Roger (Relations industrielles / Industrial Relations, 1953)
The article briefly reviews "Report 7: Employee Welfare and Benefit Programs, Proceedings of a Conference, November 1950," (49 pages).